Multihop communications in software defined vehicular networks - Domingos, Hugo Miguel Ventura (2024)
Vehicular Networks facilitate communication between vehicles and road infrastructure, thereby enabling a range of safety and convenience services, including real-time emergency notifications and updates on the road, as well as entertainment applications. However, the dynamic nature of vehicular environments, in which rapid node mobility results in frequent topology changes and fluctuating connectivity, presents a considerable challenge. These include ensuring quality of service, maintaining reliable connectivity, and securing bandwidth under highly variable traffic loads. It is often the case that traditional vehicular routing protocols are unable to cope with the demands of such rapidly evolving network conditions, particularly when there are frequent handovers which disrupt data transmission, increasing the network overload and the complexity of the network management. Software-Defined Networking (SDN) has emerged as a powerful architecture to address the challenges of these networks by leveraging its flexible and adaptive control paradigm, which allows for more effective management of the dynamic topology and mobility patterns typical of vehicular networks. The separation of the control and data planes facilitates the management of networks, enabling a centralized and responsive approach to routing decisions and resource allocation. Such flexibility becomes even more beneficial when combined with multihop routing. This Dissertation presents a solution that integrates multihop communication within software-defined vehicular networks. It implements a solution capable of performing this type of communication while taking advantage of a centralized controller that maintains an up-to-date overview of the network state. This is achieved through the developed monitoring services, which compute metrics relative to each link quality and expected lifetime, by utilizing the mobility information provided by C-ITS messages. In addition, a routing algorithm was designed that provides traffic differentiation between TCP and UDP protocols, selecting and adjusting paths that align with the specific nature and requirements of each protocol. A comparative evaluation conducted on a testbed demonstrated the superiority of the proposed algorithm over a conventional routing approach in terms of stability and quality of service, including inter-vehicles routing and to the infrastructure. This work improves the reliability of vehicular communication, paving the way for future advancements in intelligent transportation systems.